Impact of ovarian function suppression in premenopausal women with estrogen receptor-positive early breast cancer. Issue 1 (January 2019) - Lambertini, Matteo; Viglietti, Giulia; de Azambuja, Evandro
Abstract : Purpose of review: This manuscript aims at providing an updated overview on the role of adding ovarian function suppression to tamoxifen or an aromatase inhibitor as adjuvant endocrine therapy in premenopausal women with estrogen receptor-positive early breast cancer. Recent findings: Until recently, tamoxifen alone was the only recommended adjuvant treatment option for premenopausal women with estrogen receptor-positive disease. However, recent important evidence has contributed to significantly modify the endocrine treatment landscape in this setting. Summary: With the only exception of patients with low-risk clinical-pathological features characterized by excellent survival outcomes with tamoxifen alone, the use of ovarian function suppression is to be considered standard of care for most of premenopausal women with estrogen receptor-positive disease. Regarding the choice of its best partner as endocrine agent, the available data suggest that the higher the risk of disease recurrence the larger benefit can be observed with a more profound estrogen deprivation that can be obtained with ovarian function suppression and an aromatase inhibitor as compared to ovarian function suppression and tamoxifen. Despite the significant improvement in our understanding on the role of ovarian function suppression in this setting, several unanswered questions remain and further research efforts are needed in the field.